IBM PEMBANGUNAN PARIWISATA BERKELANJUTAN PAKET WISATA OUTBOND INGKUNG KWALI DI DUSUN KALAKIJO - Fadia Fitriyanti; Yordan Gunawan (LP2M Universitas Hasanuddin, 2019)
Abstract. The Kalakijo Community has recently established a Tourism Centre, which functions as a traditional culinary center for Javanese Chicken Culinary